2009
DOI: 10.3390/molecules14051825
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormones as Important Biologically Active Molecules – Their Simple Simultaneous Detection

Abstract: Phytohormones, their functions, synthesis and effects, are of great interest. To study them in plant tissues accurate and sensitive methods are required. In the present study we aimed at optimizing experimental conditions to separate and determine not only plant hormones but also their metabolites, by liquid chromatography coupled with a UV-VIS detector. The mixture we analyzed was composed of benzyladenine, kinetin, trans-zeatin, cis-zeatin, dihydrozeatin, meta-topolin, ortho-topolin, α-naphthalene acetic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Rescue of dwarf phenotypes in LmSAPΔA20 and LmSAPΔA20-ΔAN1overexpressing tobacco lines under abiotic stress conditions by application of exogenous GA 3 The overexpression of LmSAPΔA20 and LmSAPΔA20-ΔAN1 results in dwarfism and smaller leaves in tobacco plants exposed to salt or osmotic stress under in vitro conditions [19]. To test whether exogenous GA 3 treatment could rescue this phenotype, NT tobacco plants and two homozygous transgenic plants from LmSAPΔA20 and LmSAPΔA20-ΔAN1 constructs (labeled C2, C6, D2, and D9) were treated with 100 μM GA 3 on MS solid medium supplemented with 300 mM NaCl or 300 mM mannitol.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Rescue of dwarf phenotypes in LmSAPΔA20 and LmSAPΔA20-ΔAN1overexpressing tobacco lines under abiotic stress conditions by application of exogenous GA 3 The overexpression of LmSAPΔA20 and LmSAPΔA20-ΔAN1 results in dwarfism and smaller leaves in tobacco plants exposed to salt or osmotic stress under in vitro conditions [19]. To test whether exogenous GA 3 treatment could rescue this phenotype, NT tobacco plants and two homozygous transgenic plants from LmSAPΔA20 and LmSAPΔA20-ΔAN1 constructs (labeled C2, C6, D2, and D9) were treated with 100 μM GA 3 on MS solid medium supplemented with 300 mM NaCl or 300 mM mannitol.…”
Section: Plos Onementioning
confidence: 99%
“…Perception of stressful environmental conditions induces a specific stress hormone signature specifying a proper response, which is efficient in terms of fitness. Several plant growth regulators, such as phytohormones, regulate many physiological and metabolic processes that help plants to adapt to environmental stresses [3,4]. The phytohormone gibberellin (GA), also known as gibberellic acid [5], regulates various crucial growth and developmental processes, such as seed germination, stem elongation, leaf expansion, and reproductive development, in most plant species [6].…”
Section: Introductionmentioning
confidence: 99%
“…The study of interaction between benzylaminopurines and metal ions such as Cu, Co, Fe, Pt, and Pd showed that the BAP derivative is able to create dinuclear complexes in its protonated form 57. To analyze adenine‐type cytokinins, attention was paid to chromatography (HPLC/MS, HPLC/ED GC/MS), immunochemical methods (ELISA, RIA) 2,8,9 and electrochemical methods 2,10. From the electroanalytical point of view adenine and its derivatives, including 6‐BAP, represent a group of substances with typical redox properties.…”
Section: Introductionmentioning
confidence: 99%
“…Two common methods for qualification and quantification of cytokinins are mass spectrometry (MS) and immunoassays. Because of its high sensitivity and selectivity, MS coupled with liquid chromatography (LC) has become increasingly popular . Although the effective range and the sensitivity of the immunoassay are similar to those of LC/MS, there are some problems with immunoassays, including cross‐reactivity, imperfect validation and variable results for analyses of plant sample .…”
mentioning
confidence: 99%
“…Because of its high sensitivity and selectivity, MS coupled with liquid chromatography (LC) has become increasingly popular. [11][12][13][14] Although the effective range and the sensitivity of the immunoassay are similar to those of LC/MS, there are some problems with immunoassays, including cross-reactivity, imperfect validation and variable results for analyses of plant sample. [15] Using MS, it is possible to identify a compound by simple interpretation of the mass spectrum; however, a more thorough analysis includes comparison of the obtained mass spectrum with that of a standard.…”
mentioning
confidence: 99%